3d modelling of rockfall hazard at Gunung Lang, Ipoh - Muhammad Fahmi Abdul Ghani; Norbert Simon; Tuan Rusli Tuan Mohamed; Rodeano Roslee (IOP Publishing Ltd, 2022)
Densely populated hillside regions in humid tropical climatic zones are often prone to various types of mass movement. The development in Kinta Valley is no exception from the rapid development and has prompted the opening of new areas approaching slopes. This type of activity ultimately increased the level of rockfall vulnerability in this area. In this research, we conducted an assessment on the hazard level of Gunung Lang and created a 3D hazard model using the CONEFALL software. Aerial photograph, Landsat ETM+ image and DEM data of Gunung Lang were used in this study for lineament tracing and subsequently used to identify rockfall source and generated a 3D model of our study area using a high-resolution DEM. Based on our model, the maximum velocity of rockfall is approximately 36ms-1 and could travel up to 113 m from its source. Therefore, in order to minimize casualty and property damage, regular monitoring of slope failure are needed.